2020
DOI: 10.3389/fonc.2019.01545
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in Tumor-Infiltrating Lymphocytes and Vascular Normalization in Breast Cancer Patients After Neoadjuvant Chemotherapy and Their Correlations With DFS

Abstract: Objective: Changes in the number of various tumor-infiltrating lymphocytes (TILs) and degrees of vascular normalization in breast cancer (BC) patients after neoadjuvant chemotherapy (NAC) were analyzed to screen key factors that can predict the prognosis. Methods: HE-stained sections were used to assess the degree of TILs infiltration; immunohistochemically stained sections were used to assess the infiltration of CD8+, CD4+, FOXP3+ Tregs and the expression of PD-L1; immunofluorescence-stained sections were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…However, others have challenged this notion by either showing a lack of correlation of Treg abundance with survival [ 47 ] or by showing that abundance of Treg was associated with better survival in some cancers [ 48 ], including TNBC [ 49 , 50 , 51 ]. For instance, Treg identified by IHC was associated with the efficacy of NAC in breast cancer patients [ 52 ]. Furthermore, our group and others have found that abundance of Treg in metastatic tumor was lower than that in primary tumors [ 53 , 54 ], which appears paradoxical considering metastatic tumors are far more aggressive than the primary cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, others have challenged this notion by either showing a lack of correlation of Treg abundance with survival [ 47 ] or by showing that abundance of Treg was associated with better survival in some cancers [ 48 ], including TNBC [ 49 , 50 , 51 ]. For instance, Treg identified by IHC was associated with the efficacy of NAC in breast cancer patients [ 52 ]. Furthermore, our group and others have found that abundance of Treg in metastatic tumor was lower than that in primary tumors [ 53 , 54 ], which appears paradoxical considering metastatic tumors are far more aggressive than the primary cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-infiltrating immune cells affect the efficacy of radiotherapy, chemotherapy, or immunotherapy, and thus the prognosis of cancer patients (30)(31)(32). We showed that GAD1, SPP1, and WFS1 were markedly positively correlated with diverse immune cells, including B cells, CD8+T cells, CD4+T cells, macrophages, neutrophils, and dendritic cells in HCC.…”
Section: Discussionmentioning
confidence: 91%
“…It is known that tumour‐infiltrating immune cells (TIICs) play a vital prognostic role in BC patients. 8 , 9 , 10 For instance, high levels of tumour‐infiltrating lymphocytes generally indicated a favourable prognosis. 11 , 12 Another breakthrough is genetic sequencing widely applied in the individualized treatment and prognosis of BC patients.…”
Section: Introductionmentioning
confidence: 99%